BRAF V600E mutation mediates invasive and growth features in ameloblastoma - Zhang, Chen‐Xi; Zhang, Lin‐Zhou; Lin, Hao; Man, Qi‐Wen; Liu, Bing (Oral diseases, 2024)
Objectives Ameloblastoma (AM), a locally aggressive tumor with extensive growth capacity, causes significant damage to the jaw and affects facial appearance. Although the high prevalence of BRAF V600E mutation in AM is known, its specific impacts on patients with AM remain unclear. Thus, the present study investigated the role of BRAF V600E mutation, thereby focusing on its impact on AM invasion and growth. Materials and Methods Immunohistochemical analysis was used to compare BRAF V600E, MMP2, MMP9, and Ki‐67 expressions in AM (n = 49), normal oral mucosa (NOM) (n = 10), and odontogenic keratocyst (OKC) (n = 15) tissues. AM was further classified according to the presence or absence of BRAF V600E. The relationship between BRAF V600E and invasion as well as growth was evaluated. In addition, correlation analysis was performed using immunohistochemistry and confirmed via double‐labeling immunofluorescence. Finally, comparative analyses using mass spectrometry, immunohistochemistry, and immunofluorescence were performed to explore and identify underlying mechanisms. Results AM exhibited a higher incidence of BRAF V600E mutation than NOM and OKC. BRAF V600E expression was positively correlated with the invasion‐associated proteins MMP2 and MMP9 and the growth‐related protein Ki‐67. Proteomic data revealed that BRAF V600E primarily activates the MAPK signaling pathway in AM, particularly driving the phosphorylation of extracellular signal‐regulated kinase 1/2 (ERK1/2). Conclusions In summary, the findings suggested that the BRAF V600E mutation enhances the invasion and growth abilities of AM via the MAPK/ERK signaling pathway. Thus, targeting BRAF V600E or the MAPK/ERK pathway may be a potential AM therapy.